DFT study on addition reaction mechanism of guanine‐cytosine base pair with OH radical. (23rd March 2015) - Li, Minjie; Diao, Ling; Liao, Xiaofei; Kou, Li; Lu, Wencong
<x xml:space="preserve">Abstract</x> The addition reaction mechanism of OH radical with guanine‐cytosine (G.C) base pair has been explored at the B3LYP/DZP++ level of density functional theory (DFT). Structures perturbations along the hydroxylation of G.C base pair cause strain in the pairing and double‐strand breaks in DNA. Seven possible hydroxylation reactions are exothermic, and the reaction energy decreases in the order of G.CC4 > GC5.C > GC2.C > GC4.C > G.CC5 > G.CC6 > GC8.C. The hydroxylation reactions at G.CC5 and GC8.C sites appear to be barrierless, and the sequence of the barrier energy is G.CC4 > GC4.C > GC2.C > GC5.C > G.CC6 > G.CC5 ~ GC8.C. The results indicate that hydroxylation at GC8.C, G.CC5 and G.CC6 are more thermodynamically and kinetically favorable than other sites in G.C base pair. Considering the solvent effects by using the polarizable continuum model, the stabilities of all the compounds are increased significantly. Little change is taken place on the data of the reaction energies and barrier energies. Their sequences and the stability order follow the same trends like them in gas phase. The fluctuation of natural bond orbital charge further confirms that the hydroxylation reactions are exothermic. And transient spectra computed with the time‐dependent density functional theory (TD‐DFT) match well with the previous experimental and theoretical reports. Our deduced mechanism is in good agreement with the experimentally observed hydroxylated adducts. Copyright © 2015 John Wiley & Sons, Ltd.